2018
DOI: 10.29312/remexca.v4i6.1155
|View full text |Cite
|
Sign up to set email alerts
|

Germinación y características de plántulas de variedades de albahaca (Ocimum basilicum L.) sometidas a estrés salino

Abstract: La albahaca (Ocimum basilicum L.) es una especie que presenta variabilidad en la tolerancia a distintos tipos de estrés abiótico y se considera una planta sensible a la salinidad en las etapas iniciales de su crecimiento. El objetivo del presente estudio fue determinar el efecto de la salinidad en la germinación de albahaca. Veinte variedades se sometieron a tres concentraciones de NaCl (0, 50 y 100 mM) en un diseño completamente al azar con cuatro repeticiones. El trabajo se desarrolló en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…A. cristata germination started on day 6 for T 2 , day 7 for T 1 , day 8 for T 3 , day 10 for T 4 , while Previous studies indicate that plant species do not respond equally to the effects of salts 17,34,39,40 , the adverse effects of salinity in forage species vary according to the genetic hereditary character [41][42][43] .…”
Section: Figure 2 Comparison Of Means Of the Germination Capacity Undmentioning
confidence: 96%
See 1 more Smart Citation
“…A. cristata germination started on day 6 for T 2 , day 7 for T 1 , day 8 for T 3 , day 10 for T 4 , while Previous studies indicate that plant species do not respond equally to the effects of salts 17,34,39,40 , the adverse effects of salinity in forage species vary according to the genetic hereditary character [41][42][43] .…”
Section: Figure 2 Comparison Of Means Of the Germination Capacity Undmentioning
confidence: 96%
“…The excessive accumulation of ions, of Cl-or Na + in the soil solution, could be toxic for most species [12][13][14] . If have the ability to control the transport and absorption of Na + to the photosynthetic tissue, have the ability to tolerate salinity 15,16 , mainly in the germination stage, but also it is crucial in the beginning of development and growth 17,18 . Many species have tolerance to salts by polygenic inheritances, which have the ability to withstand osmotic and ionic stress at cellular level [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…With toxic ions can inhibit the absorption of water by the roots [50][51][52][53] . Species that were subjected to different saline concentrations, showed greater sensitivity than others at the time of the beginning of their development [54][55][56][57][58][59] . In a flat area with outcrops of salts at more than 3600 altitude with extreme climatic factors, it has been observed that salinity negatively affects the epidermal cell division of the root and the elongation rate, these effects affected the area part of the species causing a decrease in their yields The sowing technique, six species were seriously affected by salinity and had heterogeneous behaviors in the emergence of 58 to 86%, it should be clarified that in 22 dS m -1 they did not manage to emerge (table 2), these results reveal that the high concentrations of salts increase the potential forces of the water in the soil solution and are consistent with the announcements that the presence of solutes produces the decrease of the osmotic potential of the soil solution 12,[60][61][62] , it is also mainly related to the low hydric potential of the solution surrounding the seed [63][64][65][66] , which suggests that there is a combination of osmotic and toxic effects of the salinity.…”
Section: Fig 3 Difference Between Sowing (A) and Transplantation (B)mentioning
confidence: 99%
“…que no se trataron con NaM disminuyeron significativamente el E, pues fue evidente que el NaM contrarrestó los efectos de la salinidad, como se observó en los tratamientos NaM-7 CH y NaM-13 CH, con la única excepción de la interacción CE 12.5 dSm -1 / NaM-13 CH. Estos resultados coinciden con los estudios de Reyes-Pérez et al (2013), quienes obtuvieron en plántulas de Ocimum basilicum L. valores mayores de E a medida que disminuían las concentraciones salinas. Batista-Sánchez et al (2015), al someter tres variedades de albahaca a dosis de NaCl y de FitoMas-E ® y evaluar la E, observaron que las tres variedades incrementaron la E cuando se aplicó FitoMas-E ® , un atenuador del estrés salino, con un incremento entre 14 y 43 por ciento respecto a las plantas del tratamiento control, cuando se sometieron a niveles de estrés salino de 50 y 100 mM.…”
Section: Natrum Muriaticum Mitiga Estrés Salino En Acelgaunclassified